English for Communication: A Documentary Study on Development Approaches - Kittipanyo (Chanhorm), Phramaha Somchai; Pimrat, Lalita; Saewram, Suwit (Journal of Applied Humanities Studies, 2025)
This study aims to investigate approaches for developing English communication skills in the Thai educational context using documentary research methodology. Data were collected and analyzed from academic documents, research articles, and secondary sources related to English for communication teaching and learning. The study compiled data from various academic databases between 2019-2024, totaling 85 documents. Data analysis employed content analysis and document synthesis methods. The findings revealed that effective approaches for developing English communication skills comprise five main approaches: 1) Communicative Approach, 2) Digital Technology Integration for Learning, 3) Integrated Skills Learning, 4) Authentic Learning Contexts, and 5) Communicative Assessment. This study provides recommendations for curriculum development and English teaching methods focusing on communication in the Thai context. The research contributes valuable insights for educators, teachers, and policymakers in developing effective curricula and teaching methodologies that emphasize practical communication skills, ultimately enhancing the quality of English language education in Thailand and preparing Thai learners to compete effectively on the global stage.